Le discours (auto)promotionnel : entre la rhétorique et le marketing - Lucica MOȚOC (ACROSS)
(Self-)promotional speech is a field that lies at the intersection of rhetoric and marketing, as it involves highlighting qualities, achievements and products with the aim of convincing and arousing the interest of the target audience.